Infrared furnace for in situ neutron single‐crystal diffraction studies in controlled gas atmospheres at high temperatures. Issue 3 (25th May 2021) - Magro, Fernando; Ceretti, Monica; Meven, Martin; Paulus, Werner
Abstract : This paper reports the implementation of an infrared furnace, suitable for in situ single‐crystal neutron diffraction, working at temperatures of up to 1000°C with different and adjustable partial gas pressures up to 2 bar. Abstract : To understand oxygen diffusion mechanisms in non‐stoichiometric oxides, the possibility to explore structural changes as a function of the oxygen partial pressure with temperature and related oxygen bulk stoichiometry is mandatory. This article reports on the realization of a high‐temperature furnace, suitable for single‐crystal neutron diffraction, working continuously at temperatures of up to 1000°C at different and adjustable partial gas pressures of up to 2 bar (1 bar = 100 kPa). This allows exploration of the phase diagrams of non‐stoichiometric oxides under in situ conditions and controlled oxygen partial pressure. As a pilot study, the structural changes of Pr2 NiO4+δ were explored at room temperature (δ ≃ 0.24) and at 900°C under 1 bar P (O2 ) (δ ≃ 0.13) as well as under secondary vacuum (approximately 10 −5  mbar) conditions yielding a δ close to zero. The strong anharmonic displacements of the apical oxygen atoms along the [110] shallow diffusion pathway, which were previously observed at room temperature and 400°C, become more isotropic at 900°C. The study shows that the anisotropic oxygen displacements, here related to lattice instabilities, play a major role in understanding oxygen diffusion pathways and related activation energies at moderate temperatures. This also shows the importance of the availability of reaction cells for single‐crystal neutron diffraction to explore the phase diagram and associated structural changes of non‐stoichiometric oxygen ion conductors and respective diffusion mechanisms.